Concurrent fluorescence and volumetric optoacoustic tomography of nanoagent perfusion and bio-distribution in solid tumors - Chen, Zhenyue; Dean-Ben, Xose Luis; Liu, Nian; Gujrati, Vipul; Gottschalk, Sven; Ntziachristos, Vasilis; Razansky, Daniel (Biomedical Optics Express, 2019)
Intravenously administered liposomes and other nano-sized particles are known to passively accumulate in solid tumors via the enhanced permeability and retention (EPR) effect, which is extensively explored toward the improvement of diagnosis and drug delivery in oncology. Agent extravasation into tumors is often hampered by the mononuclear phagocytic and renal systems, which sequester and/or eliminate most of the nanoparticles from the body. Dynamic imaging of the tumor microcirculation and bolus perfusion can thus facilitate optimization of the nanoparticle delivery. When it comes to non-invasive visualization of rapid biological dynamics in whole tumors, the currently available preclinical imaging modalities are commonly limited by shallow penetration, lack of suitable contrast or otherwise insufficient spatial or temporal resolution. Herein, we demonstrate the unique capabilities of a combined epi-fluorescence and optoacoustic tomography (FLOT) system for characterizing contrast agent dynamics in orthotopic breast tumors in mice. A liposomal indocyanine green (Lipo-ICG) preparation was administered intravenously with the time-lapse data continuously acquired during and after the injection procedure. In addition to the highly sensitive detection of the fluorescence agent by the epi-fluorescence modality, the volumetric multi-spectral optoacoustic tomography readings further enabled resolving deep-seated vascular structures with high spatial resolution and hence provided accurate readings of the dynamic bio-distribution of nanoparticles in the entire tumor in 3D. The synergetic combination of the two modalities can become a powerful tool in cancer research and potentially aid the diagnosis, staging and treatment guidance of certain types of cancer in the clinical setting.
CRIS-Team Scopus Importer:2023-03-08